Association between sarcopenia and diabetes: a systematic review and meta-analysis of observational studies - Veronese, Nicola; Pizzol, Damiano; Demurtas, Jacopo; Soysal, Pinar; Smith, Lee; Sieber, Cornel; Strandberg, Timo; Bourdel-Marchasson, Isabelle; Sinclair, Alan; Petrovic, Mirko; Maggi, Stefania (European Geriatric Medicine, 2019)
Purpose: Sarcopenia and diabetes are two common conditions in older people. Some recent literature has proposed that these two conditions can be associated. However, to date, no attempt has been made to collate this literature. Therefore, we aimed to summarize the prevalence of sarcopenia in diabetes (and vice versa) and the prevalence of sarcopenia in people with diabetes complications, through a systematic review and meta-analysis. Methods: Two authors searched major electronic databases from inception until March 2019 for case control/cross-sectional/longitudinal studies investigating sarcopenia and diabetes. The strength of the reciprocal associations between sarcopenia and diabetes was assessed through odds ratios (ORs) with 95% confidence intervals (CIs), adjusted for potential confounders, where possible. Results: From 953 potential eligible articles, 20 were included in the systematic review, with 17 providing data for meta-analysis. Overall, 54,676 participants were included (mean age = 65.4 years). Diabetic participants had an increased prevalence of sarcopenia compared to controls (n = 10; OR = 1.635; 95% CI 1.204–2.220; p = 0.002; I 2 = 67%), whilst, after adjusting for potential confounders, sarcopenia was associated with an increased odds of having diabetes (OR = 2.067; 95% CI 1.396–3.624; p < 0.0001; I 2 = 0%). In 1868 diabetic participants with a complication, there was an increased prevalence of sarcopenia (OR = 2.446; 95% CI 1.839–3.254; p < 0.0001; I 2 = 0%), as compared with those with no complication. Very limited data existed regarding studies with a longitudinal design. Conclusions: Our study suggests a bidirectional association between diabetes and sarcopenia, particularly when diabetic complications are present.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Diabetes; Meta-analysis; Physical performance; Sarcopenia